2021
DOI: 10.1186/s40794-021-00155-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices toward COVID-19 among the international travelers in Thailand

Abstract: Background International travel is among the leading impactful factors of COVID-19 transmission; thus, adequate knowledge, good attitude and good preventive practices toward COVID-19 for international travelers are particularly essential for successful pandemic control. Methods A cross-sectional, questionnaire-based study was conducted to determine knowledge, attitude and practices (KAP) of international travelers (both Thai and non-Thai) and expat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 22 publications
10
9
0
Order By: Relevance
“…The current findings revealed that participants generally had positive attitudes regarding “new normal” guidelines, similar to previous reports ( 28 , 41 ). We found that 82.6% of participants agreed that “It's important to maintain a distance of at least 2 meters to prevent the spread of COVID-19,” which is similar to the findings of a previous study in Bangladesh ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The current findings revealed that participants generally had positive attitudes regarding “new normal” guidelines, similar to previous reports ( 28 , 41 ). We found that 82.6% of participants agreed that “It's important to maintain a distance of at least 2 meters to prevent the spread of COVID-19,” which is similar to the findings of a previous study in Bangladesh ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 95.5% of participants always wore masks when they went to public places. The findings were similar to those of a study conducted among Thai travelers ( 41 ). The results revealed that participants who were single engaged in prevention practices less frequently than those who were divorced or separated, consistent with a study in Bangladesh ( 45 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations